The impact of antihypertensive treatment initiation on health-related quality of life and cardiovascular risk factor levels: a prospective, interventional study - Tahkola Aapo; Korhonen Päivi; Kautiainen Hannu; Niiranen Teemu; Mäntyselkä Pekka (BMC, 2022)
Background: Effective prevention and treatment of hypertension is one of the most potential interventions in terms of preventing cardiovascular deaths and disabilities. However, the treatment control is often poor. This may be partly explained by the impact of hypertension diagnoses and treatment on health-related quality of life. Quality of life is also an important outcome for a hypertensive patient. Most of the previous studies on health-related quality of life in hypertension have concentrated on patients with treated hypertension and less is known about the initiation of medication and the first treatment year.
Methods: In this interventional study, we followed 111 primary care patients with newly diagnosed hypertension in real world primary care setting in Finland for 12 months.
Results: We found significant decrease in both systolic and diastolic blood pressure levels, as well as modest decrease in cholesterol levels and alcohol consumption. However, the health-related quality of life also slightly deteriorated during the first treatment year.
Conclusions: Our study shows that the initiation of hypertension treatment results in cardiovascular risk decrease among newly diagnosed Finnish hypertensive patients, but it is accompanied by small negative impact on health-related quality of life. However, the deterioration in health-related quality of life is of small magnitude and earlier research demonstrates several measures to enhance treatment and avoid impairment in health-related quality of life. Trial registration ClinicalTrials NCT02377960 (Date of registration: 04/03/2015).